A sleeping giant: the historically neglected Brazilian fishing sector. (1st August 2021) - Neto, José Belquior Gonçalves; Goyanna, Felipe Augusto de Alencar; Feitosa, Caroline Vieira; Soares, Marcelo Oliveira
Abstract: Since the beginning of the decade of the oceans (2021–2030), many countries failed to even develop minimal fisheries management. In some countries, where legislation is appropriately applied to the logistics of marine fishing operations, some measures of containment and fisheries management are being implemented. However, other countries have no effective plans for the sustainable development of the sector. In this paper, we have compiled information on the historical discrepancies in fisheries management in the extensive Brazilian waters and used it to illustrate the institutional neglect of this important blue-economy sector. Since the 1930s, when the first management agencies were registered, fisheries management has been handled by at least 10 different federal agencies. This discontinuity has resulted in a country that is ignorant, overall, of the quantity fished, where fishing occurs, and the status of its fish stocks. The only available long-term fishing production data is held by small state departments or marine protected areas and does not come close to reflecting the total catch of the country, with its continental dimensions and its mix of artisanal and industrial fisheries. For this reason, the present work has compiled information on the years of neglect in the governance of the fishing sector. In addition, we suggest the creation of a pivotal management model, based on three main pillars, for sustainable fisheries development. Graphical abstract: Image 1 Highlights: We demonstrate the many discontinuities in fisheries management since the 1930s. Around 10 different federal institutions have handled fisheries management. There has been no collection of fishing data or national fishing statistics for at least 10 years. Co-management, productive logistics, investments, and resource and social management are required.